Some Annotations to the Family Book of the Draft Civil Code - Rodríguez Iturri, Róger (1983)
The work deals with several annotations related to the Family Book re-formulated with the Civil Code Project. In particular, some specific clarifications are made on several aspects found in the sections Basic Norms, Impediments, Celebration of Marriage, Proof of Marriage, Invalidity of Marriage, Duties and Rights arising from Marriage, Separation of Bodies and Divorce. With respect to this last section, the implications of expanding the grounds for divorce in Peru by one more. On this point, two rival positions confront each other: one considers that marriage harbors in its very entrails a principle and an end of public interest, and the other, those who aspire to their own interest and personal satisfaction, defending the validity of divorce. However, since not enough progress has been made in Peru in the matter of causality for divorce, the following formula is suggested: “No one can invoke his or her own act”. With this, the spouse who incurs in one (s) of the aggravating causes can’t judicially raise such fact to request the dissolution of the bond, rather, this will be the power of the aggrieved spouse.